Advances in Medical Physics 2012. Issue 4 (14th March 2013) - Yester, Michael
Abstract : Advances in Medical Physics 2012. Wolbarst, Anthony B. Patrizio Capasso, Devon Godfrey, Ronald Price, Bruce Whiting, and William R. Hendee. Medical Physics Publishing, Madison, WI, 2012. 330 pp. Price: 115.00. ISBN: 9781930524569 (hardcover).